Ecotoxicological assessment of commercial boron nitride nanotubes toward Xenopus laevis tadpoles and host-associated gut microbiota. Issue 1 (2nd January 2021) - Evariste, Lauris; Flahaut, Emmanuel; Baratange, Clément; Barret, Maialen; Mouchet, Florence; Pinelli, Eric; Galibert, Anne Marie; Soula, Brigitte; Gauthier, Laury
Abstract: Despite the growing interest for boron nitride nanotubes (BNNT) due to their unique properties, data on the evaluation of the environmental risk potential of this emerging engineered nanomaterial are currently lacking. Therefore, the ecotoxicity of a commercial form of BNNT (containing tubes, hexagonal-boron nitride, and boron) was assessed in vivo toward larvae of the amphibian Xenopus laevis . Following the exposure, multiple endpoints were measured in the tadpoles as well as in bacterial communities associated to the host gut. Exposure to BNNT led to boron accumulation in host tissues and was not associated to genotoxic effects. However, the growth of the tadpoles increased due to BNNT exposure. This parameter was associated to remodeling of gut microbiome, benefiting to taxa from the phylum Bacteroidetes. Changes in relative abundance of this phylum were positively correlated to larval growth. The obtained results support the finding that BNNT are biocompatible as indicated by the absence of toxic effect from the tested nanomaterials. In addition, byproducts, especially free boron present in the tested product, were overall beneficial for the metabolism of the tadpoles.